Beginning C♯ 2008 : from novice to professional - Gross, Christian (Expert's voice in .NET., 2007)
Learn C♯ and everything you need to begin building your own applications, as well as Visual Studio IDE to create, debug, and deploy these applications. Also discover the huge range of supporting technologies that the .NET Framework offers--LINQ, ASP.NET AJAX, ADO.NET 3.0, WPF, WCF, and Windows Workflow.